EVALUASI KEBIJAKAN PENEMPATAN TENAGA KESEHATAN DI PUSKESMAS SANGAT TERPENCIL DI KABUPATEN BUTON - Mubasysyir Hasanbasri, Herman Laksono Trisnantoro (Jurnal Kebijakan Kesehatan Indonesia, 2013)
Background: One of the important elements and verydetermining and expected can become innovator in the effortof increasing the quality of health service is health force. Theplacement of health force especially in the very remote publichealth center is meant for the equalization of access to healthservice, but in fact the placement of health force policy in thevery remote public health center in Buton Regency is not yetfully implemented. Besides, the interest and motivation of thosewho are placed in the very remote areas are very low, althoughthey are placed, they will not stay for long. We observe thehigh demand for request to transfer to the urban area, resultingin the accumulation of health force in the urban public healthcenter.Method: It is a descriptive research, with qualitative methodto evaluate the placement of health force policy in the veryremote public health center in Buton Regency.Result: The placement policy is influenced by geographicalfactor and the intervention of stakeholders in the Regency.Doctor, nurse and midwife forces placed in the very remotepublic health center do not have high retention rate to stay andwork in the very remote public health center. The small incomeproduced due to unavailability of additional incentive, the unclearcarrier development pattern and lack of appreciation for thosewho work in the very remote public health center are the mainreason to request for a transfer. The transfer is conducted tothe other public health center in the same region or to the otherregency. The provision of supporting facilities policy is notable to make the health forces have motivation to stay andwork in the very remote public health center.Conclusion: The placement of health force policy can notovercome the lack of health force in the very remote publichealth center yet. The unavailability of incentives and unclearcarrier development and lack of appreciation are the mainreason why the health forces do not stay for long, resulting inlow health force number in the very remote public health center.Keyword: Placement policy, financial, supporting facilities,retention